Factors predicting health‐related quality of life in pediatric liver transplant recipients in the functional outcomes group. (1st August 2013) - Alonso, Estella M.; Martz, Karen; Wang, Deli; Yi, Michael S.; Neighbors, Katie; Varni, James W.; Bucuvalas, John C.; ,
Abstract Data from 997 pediatric LT recipients were used to model demographic and medical variables as predictors of lower levels of HRQOL. Data were collected through SPLIT FOG project. Patients were between 2 and 18 yr of age and survived LT by at least 12 months. Parents and children (age ≥ 8 yr) completed PedsQL™ 4.0 Generic Core and CF Scales at one time point. Demographic and medical variables were obtained from SPLIT. HRQOL scores were categorized as "poor" based on lower 25% of scores for each measure. Logistic regression models were generated. Single‐parent households (OR 1.94, CI 1.13–3.33, p = 0.017), anti‐seizure medications (OR 3.99, CI 1.26–12.70, p = 0.019), and number of days hospitalized (OR 1.03, CI 1.01–1.06, p = 0.0067) were associated with lower self‐reported HRQOL. Parent data identified increasing age at transplant, age 5–12 yr at survey, hospitalization >21 days at LT, re‐operations, diabetes, and growth failure at LT as additional predictors of generic HRQOL. Male gender, single‐parent households, higher bilirubin levels at LT, and use of anti‐seizure medication predicted lower cognitive function scores. HRQOL following pediatric LT is related to medical and demographic variables.